A flow-through enzymatic microreactor immobilizing lipase based on layer-by-layer method for biosynthetic process: Catalyzing the transesterification of soybean oil for fatty acid methyl ester production. (March 2017) - Bi, Yicheng; Zhou, Hua; Jia, Honghua; Wei, Ping
Graphical abstract: Highlights: Open-tube enzyme microreactor was successfully developed using commercial PTFE microtube and facile methods. Self-oxidation of dopamine was applied to modify the inner surface of PTFE for further modification. Lipase loading in open-tube microreactor was improved by multi-layer assembly. 95% conversion rate can be achieved in 53 minutes using enzyme microreactor with much higher production efficiency. Abstract: A simple and convenient method was proposed in this paper to develop a flow-through enzymatic micro-reactor made from polytetrafluoroethylene (PTFE). It consisted of the polydopamine layer (functioned as a primer) and layer by layer (LBL) coatings composed of polyethylenimine (PEI) and lipase. The multiple deposition of PEI and lipase was the key factor of increasing the enzyme loading on microreactor. After 8 PEI/lipase layers, enzyme loading on the inner surface of 5-m microchannel reached a maximum (350 μg to 400 μg), compared with approximately 20 μg in single layer. Microreactor with higher enzyme loading was successfully applied on transesterification of soybean oil for effective fatty acid methyl ester (FAME, biodiesel) production. A 95.2% conversion rate of biodiesel can be achieved in 53 min under optimized conditions, instead of a couple of hours in the traditional batch reaction.